Sclerosing peritonitis with unilateral ovarian luteinized thecoma in a post-menopausal woman: A case report - De (Pati), Auradha (J Midlife Health, 2014)
A unique case of unilateral ovarian luteinized thecoma with sclerosing peritonitis is reported because the association between these two conditions is extremely rare. Etiology is not clearly known. A 50-year-old post-menopausal woman presented with pain abdomen and huge swelling. Pelvic contrast-enhanced computed tomography (CECT) revealed a heterogenous enhancing mass arising possibly from ovary and adherent to uterus, bowl loops, and omentum. A spindle cell neoplasm without definite features of malignancy was reported in computed tomography (CT)-guided fine-needle aspiration cytology (FNAC). Ascitic fluid was negative for malignancy. Her serum carcinoembryonic antigen (CEA) (1.1ng/ml) and CA125 (27.6μ/ml) level was within normal limits. Total abdominal hysterectomy with bilateral supracolic omentectomy, resection of part of colon, and supracolic omentectomy was done. Histopathological diagnosis was luteinized thecoma with sclerosing peritonitis. Tumor cells were immunoreactive to smooth muscle antigen (SMA) and CD 99 and non- reactive to ER, PR, Calretinine, and Cytokeratin. Patient developed post-operative sepsis and enterocutaneous fistula, which was managed conservatively and was kept in follow-up. According to current concept, in spite of its large size, wide-spread involvement, mitotic activity, and complications due to peritoneal involvement, behavior of this rare clinical entity is benign.